2012
DOI: 10.1259/bjr/34392802
|View full text |Cite
|
Sign up to set email alerts
|

Breast-specific gamma imaging as an adjunct modality for the diagnosis of invasive breast cancer with correlation to tumour size and grade

Abstract: Objectives: The purpose of this study was to determine the sensitivity of breastspecific gamma imaging (BSGI) in the detection of invasive breast cancers and to characterise the sensitivity of BSGI based on tumour size and pathological grade. Methods: 139 females with invasive carcinoma who underwent BSGI were retrospectively reviewed. Patients were injected in the antecubital vein with 20-30 mCi (925-1110 MBq) of 99m Tc-sestamibi. Images were obtained with a high-resolution, breast-specific gamma camera (Dilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
3
31
1
3
Order By: Relevance
“…1 In addition to the ability to predict a potentially insignificant disease that could be managed by active surveillance, 2 tumor extent on prostate needle biopsy has been found to correlate well with tumor volume on radical prostatectomy 3-7 and helps predict margin status, 8 extraprostatic extension, 9,10 and, in combination with other parameters, posttreatment tumor progression. [11][12][13][14][15] There are several studies of mammary carcinoma that have examined the relationship between radiologic tumor size and the subsequent size on final excision [16][17][18][19][20][21] as well as those that have evaluated the relationship between radiologic or pathologic tumor size (on excision) and the likelihood of lymph node metastasis. [22][23][24][25][26] To the best of our knowledge, however, there are no systematic studies that evaluate the relationship between tumor size/extent on breast needle biopsy specimens and corresponding definitive excision specimens.…”
mentioning
confidence: 99%
“…1 In addition to the ability to predict a potentially insignificant disease that could be managed by active surveillance, 2 tumor extent on prostate needle biopsy has been found to correlate well with tumor volume on radical prostatectomy 3-7 and helps predict margin status, 8 extraprostatic extension, 9,10 and, in combination with other parameters, posttreatment tumor progression. [11][12][13][14][15] There are several studies of mammary carcinoma that have examined the relationship between radiologic tumor size and the subsequent size on final excision [16][17][18][19][20][21] as well as those that have evaluated the relationship between radiologic or pathologic tumor size (on excision) and the likelihood of lymph node metastasis. [22][23][24][25][26] To the best of our knowledge, however, there are no systematic studies that evaluate the relationship between tumor size/extent on breast needle biopsy specimens and corresponding definitive excision specimens.…”
mentioning
confidence: 99%
“…In this study, 139 females with known invasive carcinoma and an average tumor size of 1.8 cm underwent scintimammography. Of the known 149 cancers, 146 were identified with breast-specific gamma imaging, resulting in an overall sensitivity of 98% [70].…”
Section: Molecular Breast Imagingmentioning
confidence: 99%
“…The primary inclusion criteria were: (1) pathologically confirmed invasive ductal carcinoma; (2) absence of distant metastasis; (3) absence of neoadjuvant chemotherapy or radiotherapy before BSGI; and (4) pathologic tumor size C1 cm to avoid any partial volume effect. Despite the use of high-resolution equipment, the small-fieldof-view of the breast-specific gamma camera and the small tumor size still remain as limitations [7]. Retrospective review of our database between March 2009 and September 2012 yielded 168 eligible patients.…”
Section: Patientsmentioning
confidence: 99%
“…Biological information on breast cancer is important for predicting prognosis and is mainly estimated by pathologic procedures. A few studies have reported a correlation between Tc-99m sestamibi uptake and histologic prognostic factors of breast cancer [7,8]. The prognostic value of Tc-99m sestamibi washout rate from breast cancer cells for predicting responses to neoadjuvant chemotherapy has been investigated based on its relationship with P-glycoprotein (Pgp) expression [9].…”
Section: Introductionmentioning
confidence: 99%